PENGARUH PELAJARAN PENDIDIKAN AGAMA ISLAM DALAM KENAKALAN REMAJA BAGI SISWA SMK TAMAN PENDIDIKAN PERDAGANGAN , BANDAR - Pauruja Pratama; Nur Asni; Muhammad Wahyudi (Sekolah Tinggi Agama ISLAM PANCA BUDI PERDAGANGAN, 2021)
This study aims to determine the influence and impect caused on the cultivation of PAI values containing Aqidah akhlak, basic Fiqh and also about Jinayah is very influencing especially in the scope of adolescents . Seeing today's phenomenon, the lack of religious provisions makes children age Teenagers range of actions that cause mutharad, especially watermelon Great technology and advanced informatics make it easy for them to access everything, and make things easier. Increasing prevalence of juvenile delinquency agnosa for lack of knowledge religion and also reasoning of Jinayah Law (Islamic Law) that made them lack of faith and neglect of Islamic law, causing them to easily do ugliness that can harm them and the crowd.